Pelatihan Manajemen Organisasi Dan Peningkatan Kapasitas Pemuda Bina Remaja Di Era Digital - Fitriana, Amalia Indah; Febrianto, Hendra Galuh (Jurnal Pengabdian Manajemen, 2024)
This human resource perspective has a very high population growth rate, which means that Indonesia is currently in an active working period. Therefore, the availability of labor can be used to increase development and progress throughout the country, but the government needs to increase efforts related to improving the quality of human resources. The purpose of this PKM is to increase the capacity of youth and the management of youth development organizations. Participants are members of the Youth Development of Buaran Indah Village, Tangerang City. The results of this activity showed that participants were very enthusiastic in learning about capacity building and organizational management. This is because the sharing of organizational experiences can trigger the enthusiasm and awareness of participants in organizing. The benefits of this research are expected to increase the capacity of youth in Buaran Indah village.